2015
DOI: 10.1021/acs.langmuir.5b03171
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and Structural Studies of a Surface Active Porphyrin in Solution and in Langmuir–Blodgett Films

Abstract: Controlling aggregation of the dual sensitizer-emitter (S-E) zinc tetraphenylporphyrin (ZnTPP) is an important consideration in solid state noncoherent photon upconversion (NCPU) applications. The Langmuir-Blodgett (LB) technique is a facile means of preparing ordered assemblies in thin films to study distance-dependent energy transfer processes in S-E systems and was used in this report to control the aggregation of a functionalized ZnTPP on solid substrates. This was achieved by synthetic addition of a short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 52 publications
(127 reference statements)
0
17
0
Order By: Relevance
“…High values of molar extinction coefficients of porphyrins and their appropriate luminescence quantum yields (about 10 %) supply excellent brightness to their films. Therefore, very sensitive sensors can be developed using changes of absorbance or emission of porphyrin films in the presence of metal ions and other small molecules …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…High values of molar extinction coefficients of porphyrins and their appropriate luminescence quantum yields (about 10 %) supply excellent brightness to their films. Therefore, very sensitive sensors can be developed using changes of absorbance or emission of porphyrin films in the presence of metal ions and other small molecules …”
Section: Resultsmentioning
confidence: 99%
“…However, due to the low solubility and reactivity of porphyrins in aqueous media, it is necessary to use special approaches that would ensure the binding of metal ions under physiologically and environmentally significant conditions. For this purpose, approaches based on the complexation of metal ions from their aqueous solutions by free porphyrin bases organized in Langmuir monolayers at the air/water interface[19b], or grafted onto the glass surface have been proposed. For example, a mixed monolayer composed of porphyrin and long‐chain alkyl surfactant molecules was developed to prevent the aggregation of A 4 ‐type porphyrins and facilitate the complexation of metal ions.…”
Section: Resultsmentioning
confidence: 99%
“…6,9,12 In explorations of processes that might improve the overall efficiency of NCPU-TTA, our groups have shown that homo-molecular NCPU-TTA in molecules such as d 0 or d 10 metalloporphyrins (MPs) that have unusually long-lived second excited singlet (S 2 ) states may prove useful. 5,[14][15][16][17] Homo-molecular NCPU-TTA involves photoexcitation of the porphyrin in its Q band, which in MPs with extended  electron systems can extend well into the near infrared.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports, including ones from our groups, have emphasized that the NCPU efficiencies of MPs in the solid state can be optimized by controlling the extent of aggregation and the relative spatial orientation of the aggregates formed. 2,16,17,47,48 However, the choice of matrix and its permeability by oxygen are equally important. In the latter respect, the use of PVA should favour increased efficiency because of its demonstrated oxygen-barrier properties.…”
mentioning
confidence: 99%
“…The formation of aggregates results in the quenching of emission, which in some cases limits the applicability of porphyrins as imaging agents. One approach that is used to avoid this quenching is to fix the porphyrin molecule in a 3D network, such as silica or metal organic frameworks, as we demonstrated in this work in the hydrogel matrix …”
Section: Resultsmentioning
confidence: 99%